Geospatial Assessment of the Effect of Groundwater Salinity on NDVI in Western Karbala - Ahmed, Halla H.; Al-Waeli , Aurass M.; Al-Azawi , Fadia W. (Mesopotamian Journal of Marine Sciences, 2025)
Groundwater is a vital resource for many targets, including drinking, irrigation, industry, and many other purposes. However, increasing salinity threatens this precious resource, which negatively affects its quantity and quality. This issue is especially manifested in arid and semi-arid regions, where the demand for water is increasing. The importance of this research lies in understanding the mechanisms of salinity’s impact on groundwater especially in diverse hydrological and geological contexts. This study is also looking for monitoring and surveillance the impact of changes in groundwater quality indicators in western Karbala on wheat growth using Sentinel‑2 satellite imagery. The study also evaluated the variations in the quality of groundwater particularly salinity‑related indicators, where it was expressed in terms of the values of Normalized Difference Vegetation Index (NDVI). Water samples collected in sterile, sealable plastic containers, each with a capacity of 250 ml. Water was collected several times at intervals consistent with the time of the satellite image to accurately measure the impact of groundwater quality and characteristics on plant health. Filter paper was used to remove suspended particles and impurities.The fieldwork period was distributed over several months (December, January, February, and March). This study found that there are three Total Dissolved Solids (TDS) varieties during the period of study. Therefore, the impact of the salinity of irrigation water groundwater salinity (ECw) and TDS values can be inferred from its negative impact on plant growth depending on the NDVI values, which can be monitored periodically by obtaining satellite images, That is an early warning means for any phycological damage to the plant due to the deterioration of water quality indicators and suitability for irrigation, one of the most important indicators of which is the salinity status. This approach allows a deeper understanding of the correlation between subsurface water salinity and vegetation health, which helps in making informed decisions for the management of Water Resources and agricultural land.